Santa Fé do Sul and Rubinéia (SP): conditions of urban history in the Far Northwest of the State of São Paulo - Stafusa, Vitor Mendes; Ghirardello, Nilson (Revista Nacional de Gerenciamento de Cidades, 2020)
This paper aimed to list the natural and social conditions that may have guided the dawn of some cities in the Far Northwest of São Paulo during the 20th century. Therefore, a case study was made on the urban history of Santa Fé do Sul and Rubinéia (SP) to relate the occupation and formation of cities with elements of landscape and society. The time frame that begins in the 19th century with the eviction of natives by the people of Minas Gerais, discusses the strategies of the coffee economy and the close relationship with railroads, culminating in the formation of both cities in mid-20th century. For this purpose, it was necessary a literature review regarding the occupation of the hinterland of São Paulo and the local urban history, besides a documental research in primary sources that discussed the urban spaces. The research develops qualitatively and analyzes, empirically, the initial morphology of the referred cities. The influence of the streams delimitating rural properties and how these bodies of water directed the railway was found, discovery that in turn guided the urban layout of the cities analyzed. About the social factors, it was found that Porto Taboado, Estrada de Ferro Araraquara and the socioeconomic context of the time were of great importance on forming and definition of the cities in the region. Finally, from the study of both cities, this paper discussed the historical processes that formed them and may serve as an aid for studies of urban history in the municipalities located in the same context.